Miner ID: Facilitating bitcoin as a service - Zhang, Wei (Frontiers in Blockchain, 2023)
Block production in Bitcoin, often referred to as mining, is becoming increasingly industrialized. Many nodes in the network are represented by registered business entities. The concept of Bitcoin as a Service is also pushing the industry to become more customer oriented. Services such as transaction validation, transaction status query or notification, and blockchain data indexing are in high demand among blockchain application providers and users. As service providers, nodes need to distinguish themselves from others and be identifiable. In this article, we introduce an efficient self-established identity system, called Miner ID, to enable nodes to be publicly identifiable. It is based on economic investment and active participation in the blockchain network. Moreover, Miner ID is optional for nodes, and it does not affect the consensus mechanism of the network. We explore use cases including instant transaction confirmation, blockchain attestation, public key infrastructure, and token recovery. Miner ID can also be used for secure communication with applications, services, users and peers.